2018
DOI: 10.3389/fgene.2018.00216
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Toxic Polyglycine Biosynthesis and Aggregation in Cell Models Expressing Expanded CGG Repeats

Abstract: Fragile X-associated tremor/ataxia syndrome (FXTAS) is a late-onset neurodegenerative disorder caused by expanded CGG (CGGexp) trinucleotides in the 5′UTR of the FMR1 gene encoding fragile X mental retardation protein (FMRP). The patients, with the number of the repeats ranging from 55 to 200, show specific manifestation of clinical symptoms that include intention tremor, gait ataxia, cognitive deficits, and brain atrophy. Accumulation of toxic polyglycine (FMRpolyG), a by-product of the CGGexp repeat-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…FMRP protein has been shown to be one of the leading causes of the fragile X syndrome (Zhang et al , ) as well as one of the leading causes of monogenetic forms of autism (Bassell & Warren, ; Hernandez et al , ). In addition to aggregating in diseases (Sjekloća et al , ; Derbis et al , ), FMRP is a known quadruplex‐binding protein (Zhang et al , ; Vasilyev et al , ). Future studies on whether these roles are related would be of significant interest.…”
Section: Discussionmentioning
confidence: 99%
“…FMRP protein has been shown to be one of the leading causes of the fragile X syndrome (Zhang et al , ) as well as one of the leading causes of monogenetic forms of autism (Bassell & Warren, ; Hernandez et al , ). In addition to aggregating in diseases (Sjekloća et al , ; Derbis et al , ), FMRP is a known quadruplex‐binding protein (Zhang et al , ; Vasilyev et al , ). Future studies on whether these roles are related would be of significant interest.…”
Section: Discussionmentioning
confidence: 99%
“…FMRP protein has been shown to be one of the leading causes of the fragile X syndrome (17) as well as one of the leading causes of monogenetic forms of autism (31,32). In addition to aggregating in disease (33,34), FMRP is a known quadruplex-binding protein (16,17). Future studies on whether these roles are related would be of significant interest.…”
Section: Discussionmentioning
confidence: 99%
“…We overexpressed a 100×CGG construct carrying the 5′UTR sequence of the FMR1 gene containing ~100 CGG repeats (Fig. 2a ; artificial FXTAS model) 19 , 23 . RAN translation of mRNA from this construct leads to the biosynthesis of FMRpolyG fused with GFP (FMRpolyG-GFP).…”
Section: Resultsmentioning
confidence: 99%
“…In an FXTAS cell model, some RNA-binding compounds reduced SAM68-dependent aberrant splicing and inhibited RAN translation of FMRpolyG 20 22 . In a similar cell model, we showed that antisense oligonucleotides (ASOs) complementary to the FMR1 -specific sequence downstream of the CGG repeat tract induced targeted mRNA degradation through RNase H1 recruitment and caused a significant decrease in FMRpolyG production and aggregation 23 . Recently, ASOs targeting RAN translation initiation site on mRNA was also proved to reduce biosynthesis of FMRpolyG in FXTAS cellular models 24 .…”
Section: Introductionmentioning
confidence: 99%